Enhancing Emergency Management through AI-Augmented Central Coordination: Comparative Case Studies from the USA, New Zealand, and Bangladesh (Journal of Wildlife and Conservation, 2025)
Centralized command is important for successful emergency management, especially as natural and man-made disasters are happening more often and are becoming more complicated. But most governments have problems with fragmented systems, misaligned communication, and a lack of technology integration, which makes it hard to respond quickly and effectively. This research examines coordination failures through a comparative case study involving the USA, New Zealand, and Bangladesh, focusing on both natural and anthropogenic disasters. Significant deficiencies have been recognized in command and control, interagency collaboration, and technical readiness. The research proposes a conceptual design for an AI-Augmented Central Physical Emergency Operations Center (AI-EOC) based on these discoveries. The AI-EOC is a combination of physical infrastructure and next-generation AI-enabled data analytics, real-time monitoring, and communication tools that help people understand what’s going on, make decisions, and manage resources better. The framework aims to create a scalable, adaptable, and effective method for emergency response by combining centralized coordination with smart automation to handle a wide range of crisis situations. This work will improve disaster preparedness, response, and recovery, which will show how AI may be used to improve global emergency management systems.